Activation of Dopamine Receptors in the Nucleus Accumbens Promotes Sucrose-Reinforced Cued Approach Behavior - du Hoffmann, Johann; Nicola, Saleem M. (Frontiers in Behavioral Neuroscience, 2016)
Dopamine receptor activation in the nucleus accumbens (NAc) promotes vigorous environmentally-cued food-seeking in hungry rats. Rats fed ad libitum, however, respond to fewer food-predictive cues, particularly when the value of food reward is low. Here, we investigated whether this difference could be due to differences in the degree of dopamine receptor activation in the NAc. First, we observed that although rats given ad libitum access to chow in their home cages approached a food receptacle in response to reward-predictive cues, the number of such approaches declined as animals accumulated food rewards. Intriguingly, cued approach to food occurred in clusters, with several cued responses followed by successive non-responses. This pattern suggested that behavior was dictated by transitions between two states, responsive and non-responsive. Injection of D1 or D2 dopamine receptor agonists into the NAc dose-dependently increased cue responding by promoting transitions to the responsive state and by preventing transitions to the non-responsive state. In contrast, antagonists of either D1 or D2 receptors promoted long bouts of non-responding by inducing transitions to the non-responsive state and by preventing transitions to the responsive state. Moreover, locomotor behavior during the inter-trial interval was correlated with the responsive state, and was also increased by dopamine receptor agonists. These results suggest that activation of NAc dopamine receptors plays an important role in regulating the probability of approach to food under conditions of normative satiety.